Evolution and consciousness : from a barren rocky earth to artists, philosophers, meditators and psychotherapists - DelMonte, Michael M. (Contemporary psychoanalytic studies, 2019)
This volume provides a comprehensive and accessible introduction to the emerging concept of the evolution of consciousness. The simple, but dynamic, theory of evolving consciousness blends the powerful insights of modern science with the deep wisdom of age-old cultures, synthesising the traditions of East and West, of the head and heart, of male and female and of science and spirituality. To borrow a phrase from American philosopher Ken Wilber, it is a concept that "transcends and includes" all that has gone before. By integrating diverse multi-disciplinary approaches, it provides an overarching and transcending model that moves us to a new level of meaning and understanding of our place in the world, and in so doing deepens our work as psychotherapists